2006
DOI: 10.1021/jp0650331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 on Relaxation Phenomena and Mechanism of Ion Conductivity of [Nafion/(SiO2)x] Composite Membranes

Abstract: This report describes a study of the effect of SiO2 nanopowders on the mechanism of ionic motion and interactions taking place in hybrid inorganic-organic membranes based on Nafion. Five nanocomposite membranes of the formula [Nafion/(SiO2)x] with SiO2 ranging from 0 to 15 wt % were prepared by a solvent casting procedure. TG measurements demonstrated that the membranes are thermally stable up to 170 degrees C but with the loss water it changes the cluster environments and changes the conductivity properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
258
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(313 citation statements)
references
References 50 publications
41
258
1
13
Order By: Relevance
“…22 The formation of dynamic SiO 2 … HSO 3 -crosslinks in the hydrophilic polar clusters, as indicated by the increase in the elastic modulus, influences the chain dynamics of the hydrophobic fluorocarbon domains of the host material. 22 Other studies were performed on [Nafion/(M x O y ) n ] membranes containing 5 wt% Ti, Zr, Hf, Ta and W oxides. 23,24 These studies indicated that: a) the amount of each of the four water domains detected in the bulk membranes depends on the acidity of M x O y oxocluster; b) the thermal, mechanical and electrical stability of the Nafion 1 host polymer depends on the concentration of dynamic R-SO 3 H … M x O y … HSO 3 -R cross-links in bulk material; and c) the concentration and strength of the dynamic R-SO 3 H … M x O y … HSO 3 -R cross-links occurring inside polar hydrophilic cages of the membranes increase along group IV and decrease along period VI of the periodic exhibits very favorable physicochemical properties in terms of elastic modulus and conductivity, which result from strong acid-base interactions that occur within the ion aggregate domains between HfO 2 and the sulfonic acid groups of host polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The formation of dynamic SiO 2 … HSO 3 -crosslinks in the hydrophilic polar clusters, as indicated by the increase in the elastic modulus, influences the chain dynamics of the hydrophobic fluorocarbon domains of the host material. 22 Other studies were performed on [Nafion/(M x O y ) n ] membranes containing 5 wt% Ti, Zr, Hf, Ta and W oxides. 23,24 These studies indicated that: a) the amount of each of the four water domains detected in the bulk membranes depends on the acidity of M x O y oxocluster; b) the thermal, mechanical and electrical stability of the Nafion 1 host polymer depends on the concentration of dynamic R-SO 3 H … M x O y … HSO 3 -R cross-links in bulk material; and c) the concentration and strength of the dynamic R-SO 3 H … M x O y … HSO 3 -R cross-links occurring inside polar hydrophilic cages of the membranes increase along group IV and decrease along period VI of the periodic exhibits very favorable physicochemical properties in terms of elastic modulus and conductivity, which result from strong acid-base interactions that occur within the ion aggregate domains between HfO 2 and the sulfonic acid groups of host polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The new ZrO 2 and Ta 2 O 5 -containing nanofiller is prepared with the intent of combining the improvements resulting from fillers with a ''core-shell'' morphology with the intrinsic characteristics of the individual oxides that will allow it to maintain strong R- 3 -R interactions and reduce the water uptake within the hybrid membranes. Of the group IV and period VI oxoclusters previously investigated, [22][23][24]28 32 The preparation of the nanofiller based on ZrO 2 and Ta 2 O 5 , indicated as ZrTa, is part of an effort to produce a ''chemical core-shell'' nanofiller and subsequently elucidate the effect of its chemistry and surface properties on the structure, properties and fuel cell performance of the resulting hybrid inorganic-organic membranes. 30 In addition, the water uptake, the thermal and structural properties will be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Na prática, a adição de nanopartículas cerâmicas em membranas Nafion resulta geralmente no decréscimo da condutividade protônica (σ) e o papel efetivo da segunda fase nas propriedades elétricas do Nafion não é totalmente compreendido [48]. …”
Section: Eletrólitos Compósitosunclassified
“…Na prática, a adição de nanopartículas cerâmicas em membranas Nafion resulta geralmente no decréscimo da condutividade protônica (σ) e o papel efetivo da segunda fase nas propriedades elétricas do Nafion não é totalmente compreendido [48]. As medidas de condutividade de eletrólitos compósitos reportadas variam com relação à orientação da amostra e o intervalo de temperatura medido.…”
Section: Eletrólitos Compósitosunclassified
See 1 more Smart Citation